Upaya Kantor Urusan Agama Dalam Meminimalisir Nikah Melalui Kadi Liar - Mohd. Kalam Daud; Nahara Eriyanti; Nani Ikhwana (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2021)
In Indonesia, the procedure made for the Islamic community is that the marriage must be officially registered with the competent authority and published in accordance with the Marriage Law Number 1 of 1974 and must meet the requirements and pillars so that the marriage is valid. However, some people in North Singkil District still carry out their marriages that are not officially registered and the marriages are carried out through a guardian judge who is not appointed by the Minister of Religion or an official appointed by him, who is known in the community as a wild qadi. The formulation of the problem in this study is why people marry through illegal qadi, what are the obstacles and efforts of the North Singkil Religious Affairs Office in minimizing marriage through illegal qadi. In this study the authors use field research (field research). Based on the results of the study, the reasons why the people of North Singkil married through illegal qadi were because they were pregnant out of wedlock, avoiding administrative procedures, because of dishonest intentions, lack of education and understanding about marriage, and not old enough. The obstacles faced by KUA in minimizing marriages through cadiliar are: the lack of public awareness and understanding of the law, the absence of a firm sanction for those who marry through illegal qadi, and there are still many clerics who are willing to marry off on the grounds of avoiding adultery without registering their marriages with the KUA. The efforts made by the North Singkil KUA are to disseminate information to the public about the importance of registered marriages, conduct counseling on the registration of marriages and happy families through Islamic religious educators., as well as providing an explanation of marital problems at the time of the marriage ceremony.